The localization and risk factors of squamous cell carcinoma in the oral cavity: a retrospective study of 1501 cases - Sundermann, Britta Vanessa; Uhlmann, Lorenz; Hoffmann, Jürgen; Freier, Kolja; Thiele, Oliver C. (Journal of cranio-maxillofacial surgery, 2018)
Head and neck cancer is the tenth leading cause of cancer mortality. Ninety percent of tumours in the oral cavity are squamous cell carcinomas. Information about the exact localisation of OSCC is missing in the literature. In the present study, we retrospectively analysed a total of 1501 OSCC patients, who were treated between 1975 and 2009. The purpose of this study was to examine the localisation of OSCC tumours and to analyse the influence of various parameters on tumour localisation. 71.5% of these patients were male and 28.5% were female. The mean age was 60 years. The most common sites of OSCC occurrence were the floor of the mouth and the anterior base of the mouth. The hard palate was the most affected anatomical area of the maxilla. Descriptive statistical analysis, chi-square testing and a multivariate analysis using a multinomial logistical model showed a significant correlation of younger age and female gender with tumour occurrence in the maxilla and the tongue. We provide a very detailed anatomical mapping of OSCC.